2019
DOI: 10.1093/jscr/rjz320
|View full text |Cite
|
Sign up to set email alerts
|

Endourologic treatment for a fibroepithelial ureteral polyp protruding from the urethra

Abstract: Fibroepithelial polyps (FP) of the ureter are rare and benign mesodermal tumors frequently mistaken for transitional cell carcinoma. We hereby report a rare case of a 19-year-old patient with two FPs, originating from the distal left ureter that were successfully treated with ureteroscopy. One of these polyps was completely protruding outside the bladder through the urethra, which makes this case unique in the literature. Ureteroscopy is currently the best method available for identification, histologic diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The differential diagnosis of an anatomic mass at the bladder base causing dramatic urinary obstruction and retention in a previously healthy child includes hemangioma, leiomyoma, benign bladder polyp, urethral cyst or polyp, rhabdomyosarcoma, neurofibroma, urinary bladder cystitis cystica, ureterocele, posterior urethral valves, persistent müllerian remnant, transitional cell carcinoma, and adenocarcinoma. [1][2][3][4][5][6] In our patient's case, in addition to the transurethral cystoscopic surgical findings, the histopathologic report of fibrovascular and muscular tissue with focally preserved urothelial lining and foci of granulation tissue was compatible with a diagnosis of benign fibroepithelial polyp (FEP) of the bladder base.…”
Section: Foresee Your Next Patientmentioning
confidence: 51%
See 2 more Smart Citations
“…The differential diagnosis of an anatomic mass at the bladder base causing dramatic urinary obstruction and retention in a previously healthy child includes hemangioma, leiomyoma, benign bladder polyp, urethral cyst or polyp, rhabdomyosarcoma, neurofibroma, urinary bladder cystitis cystica, ureterocele, posterior urethral valves, persistent müllerian remnant, transitional cell carcinoma, and adenocarcinoma. [1][2][3][4][5][6] In our patient's case, in addition to the transurethral cystoscopic surgical findings, the histopathologic report of fibrovascular and muscular tissue with focally preserved urothelial lining and foci of granulation tissue was compatible with a diagnosis of benign fibroepithelial polyp (FEP) of the bladder base.…”
Section: Foresee Your Next Patientmentioning
confidence: 51%
“…FEPs affecting the bladder and/or urethra are quite rare. [2][3][4][5][6][7] Histologically, FEPs of the genitourinary system are composed of a core of fibrovascular tissue lined by benign urothelium. 2,4 They are usually solitary, as seen in this patient's case, but cases of multiple isolated polyps have been reported.…”
Section: Foresee Your Next Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Current practice in human medicine is to endoscopically resect the ureteral tumor using electrocautery (Abdessater et al 2019), holmium (12 cases) or thulium laser (Sheng et al 2016) and a temporary stent can be placed to prevent constriction (Sun et al 2021, Kumar et al 2022, Buckland & Blatt 2023. If the size of the polyp is too large and the entire lumen of the ureter is blocked or the polyp is located far cranial in the ureter or in the renal pelvis percutaneous resection is performed (Lam et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Ali Momenzadeh et al reported a case of large UFP presenting a vegetative bladder mass excised ureteroscopically and recommended further assessment for any mass juxtaposed vesicoureteral junction and also suggest ureteroscopically approach to distal UFPs, it was the first report from IRAN [ 6 ]. At present, the literature has reported many similar cases of ureteral polyps extending into the bladder cavity, only one case report a UFPs with permanent extension beyond the bladder cavity through the urethra, this 19-year-old patient had two UFPs from the distal left ureter, they used cautery to remove the entire polyp under the endoscope [ 7 ]. According to the Ludwig D.J, due to advances in technology, more UFP cases had been treated by electrocautery or YAG laser through ureteroscopy since 1980s, with no reported recurrence.…”
Section: Discussionmentioning
confidence: 99%